2016
DOI: 10.1016/j.jmps.2016.07.012
|View full text |Cite
|
Sign up to set email alerts
|

On strain and damage interactions during tearing: 3D in situ measurements and simulations for a ductile alloy (AA2139-T3)

Abstract: Strain and damage interactions during tearing of a ductile Al-alloy with high work hardening are assessed in situ and in 3D combining two recently developed experimental techniques, namely, synchrotron laminography and digital volume correlation. Digital volume correlation consists of registering 3D laminography

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
37
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 60 publications
6
37
0
Order By: Relevance
“…Consequently, CT-like specimens were chosen to carry out in situ tests [35,34,38] to gain new insights into these mechanisms. The combined use of laminography [18,20,19] and global Digital Volume Correlation (DVC) [51] has enabled in situ displacement elds to be measured at the microscale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, CT-like specimens were chosen to carry out in situ tests [35,34,38] to gain new insights into these mechanisms. The combined use of laminography [18,20,19] and global Digital Volume Correlation (DVC) [51] has enabled in situ displacement elds to be measured at the microscale.…”
Section: Introductionmentioning
confidence: 99%
“…2198 (Al-Cu-Li) aluminium alloys have been studied under naturally and articially aged conditions, thereby changing the nano-precipitate structure and the work hardening behavior [35,34,53,9,38]. Representing the latest generation of aeronautical alloys, and understanding the underlying failure mechanisms is of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, DSA cannot be ignored in complex forming operations, despite possibly evanescent manifestations in monotonic loading. Recent in-situ experimental studies combining X-ray laminography and 3D digital image correlation methods during Kahn tear tests on a AA-2198-T8 rolled material, and on other similar alloys, clearly evidenced the occurrence of early plastic strain localization [13,30]. It was observed that intense plastic localization bands form away from the crack tip at the very beginning of deformation, and these bands are intermittent in time but not in space.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the above studies [13,30,26], present work contributes to further investigation in terms of modeling the role of crystal orientations, plastic anisotropy, grain neighborhood, and grain-to-grain interactions on the intensity of dynamic strain aging effects. In a recent study, simple model lamellar grain structures representative of rolled microstructures were modeled, using experimentally reported preferred crystal orientations [31].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that some damage variables such as porosity can now be observed experimentally thanks to X-ray imaging techniques [11,12,13,14]. Inclusions and voids can be studied individually based on manual [13,15] or automatic [14] procedures.…”
Section: Introductionmentioning
confidence: 99%